Fe and Fe-P Foam for Biodegradable Bone Replacement Material: Morphology, Corrosion Behaviour, and Mechanical Properties - Monika Hrubovčáková; Miriam Kupková; Miroslav Džupon (Advances in Materials Science and Engineering)
Iron and iron-phosphorus open-cell foams were manufactured by a replica method based on a powder metallurgical approach to serve as a temporary biodegradable bone replacement material. Iron foams alloyed with phosphorus were prepared with the aim of enhancing the mechanical properties and manipulating the corrosion rate. Two different types of Fe-P foams containing 0.5 wt.% of P were prepared: Fe-P(I) foams from a phosphated carbonyl iron powder and Fe-P(II) foams from a mixture of carbonyl iron and commercial Fe3P. The microstructure of foams was analyzed using scanning electron microscopy. The mechanical properties and the corrosion behaviour were studied by compression tests and potentiodynamic polarization in Hank’s solution and a physiological saline solution. The results showed that the manufactured foams exhibited an open, interconnected, microstructure similar to that of a cancellous bone. The presence of phosphorus improved the mechanical properties of the foams and decreased the corrosion rate as compared to pure iron foams.